Aortic elastic properties are related to left ventricular diastolic function in patients with type 1 diabetes mellitus. - Karamitsos, T; Karvounis, H; Didangelos, T; Papadopoulos, C; Kachrimanidou, M; Selvanayagam, J; Parharidis, G (2008)
OBJECTIVE: The aim of the study was to evaluate left ventricular diastolic function and its relation to aortic wall stiffness in patients with type 1 diabetes mellitus without coronary artery disease or hypertension. PATIENTS: Sixty-six patients with type 1 diabetes mellitus were examined by echocardiography and divided into two groups according to the diastolic filling pattern determined by mitral annulus tissue Doppler velocities. Group A patients (n = 21) presented diastolic dysfunction with a peak early diastolic mitral annular velocity (Em)/peak late diastolic mitral annular velocity (Am) ratio <1 whereas in group B patients (n = 45) the Em/Am ratio was >1. Coronary artery disease was excluded based on normal thallium scintigraphy. Aortic stiffness index was calculated from aortic diameters measured by echocardiography, using accepted criteria. RESULTS: Aortic stiffness index differed significantly among the two groups. Significant correlations were found between parameters of left ventricular diastolic function (Em/Am, isovolumic relaxation time, deceleration time) and aortic stiffness index. Multiple stepwise linear regression analysis revealed aortic stiffness index (beta = -0.39, p = 0.001) and isovolumic relaxation time (beta = -0.46, p < 0.001) as the main predictors of Em/Am ratio. CONCLUSIONS: Aortic stiffness is increased in type 1 diabetic patients with left ventricular diastolic dysfunction. This impairment in aortic elastic properties seems to be related to parameters of diastolic function.